Examining neurobehavioral effects of pesticide exposure in workers involved in mosquito control in Malaysia: A Preliminary study - Yusof, Muhammad Zubir; Semple, Sean; Cherrie, John W; Samsuddin, Niza (2017)
Pesticides are widely used in the agricultural sector and other settings. In Malaysia organophosphate and pyrethroid pesticides are commonly used to control mosquito-borne disease. This project aims to do three things: assess the exposure to pesticides of a group of workers who mix and spray pesticides to con-trol the mosquito population in Malaysia; estimate workers’ lifetime exposure to pesticides using current measurements and retrospective exposure reconstruction methods; determine if pesticide exposed workers have poorer neurobehavioral health when compared to non-exposed controls. Dermal and inhalation exposure assessment will be performed to evaluate current exposure. Workers’ exposure over their working life will be estimated using modeling techniques. Neurobehavioral tests will be carried out using paper-based questionnaires and CANTAB® computerized tests. An estimated 127 pesticide workers and a similar number of controls will be approached to take part in this study. The findings of the study will help inform the evidence base relating to long-term health effects of pesticide exposure, and increase understanding of the pesticide exposure of these workers and the effectiveness of current control measures.